Characterization of Errors and Math Anxiety in Solving Differential Equation Problems - Aini, Septi Dariyatul; Zayyadi, Moh; Surahmi, Ema (STKIP Singkawang, 2025)
This study aims to describe the errors and anxiety of students with high, medium, and low mathematical abilities in solving Differential Equation problems. This study is a qualitative descriptive study. The instruments used are the Mathematics Ability Test, the Differential Equation Problem Solving Test and interview guidelines. Based on the results of the study, information was obtained that: (1) Subjects with high mathematical abilities made procedural errors because they could not solve problems in their simplest form and met the indicators of mathematical anxiety of fear of failure; (2) Subjects with moderate mathematical abilities made procedural errors, namely not being able to solve problems in their simplest form and technical errors, namely errors in calculating the value of arithmetic operations and using the distributive property of multiplication over addition. These subjects met the indicators of mathematical anxiety, namely ability and self-confidence, difficulty concentrating, nervousness, restlessness, heart palpitations; (3) Subjects with low mathematical abilities made conceptual errors, namely errors in using formulas in answering questions and errors in using formulas that did not comply with the conditions/prerequisites for the validity of the formula; procedural errors, namely not being able to solve problems in their simplest form and not being able to continue the solution steps; technical errors, namely errors in calculating the value of an arithmetic operation. This subject meets the indicators of mathematical anxiety, namely ability and self-confidence, difficulty concentrating, fear of failure, nervousness, unhappiness, restlessness, cold sweats, heart palpitations, headaches.Karakterisasi Kesalahan dan Kecemasan Matematika dalam Menyelesaikan Soal Persamaan DiferensialABSTRAKPenelitian ini bertujuan mendeskripsikan kesalahan dan kecemasan siswa berkemampuan matematika tinggi, sedang, dan rendah dalam menyelesaikan soal Persamaan Diferensial. Penelitian ini termasuk penelitian deskriptif kualitatif. Instrumen yang digunakan adalah Tes Kemampuan Matematika, Tes Penyelesaian Soal Persamaan Diferensial dan pedoman wawancara. Berdasarkan hasil penelitian diperoleh informasi bahwa: (1) Subjek berkemampuan matematika tinggi melakukan kesalahan prosedural karena tidak dapat menyelesaikan soal pada bentuk paling sederhana dan memenuhi indikator kecemasan matematika takut gagal; (2) Subjek berkemampuan matematika sedang melakukan kesalahan prosedural yaitu tidak dapat menyelesaikan soal pada bentuk paling sederhana dan kesalahan teknik yaitu kesalahan menghitung nilai dari operasi hitung dan menggunakan sifat distributif perkalian terhadap penjumlahan. Subjek ini memenuhi indikator kecemasan matematika yaitu kemampuan dan kepercayaan diri, sulit konsentrasi, gugup, gelisah, jantung berdebar; (3) Subjek berkemampuan matematika rendah melakukan kesalahan konseptual yaitu kesalahan dalam penggunaan rumus dalam menjawab soal dan kesalahan menggunakan rumus yang tidak sesuai dengan kondisi/prasyarat berlakunya rumus; kesalahan prosedural yaitu tidak dapat menyelesaikan soal pada bentuk paling sederhana dan tidak dapat melanjutkan langkah penyelesaian; kesalahan teknik yaitu kesalahan dalam menghitung nilai suatu operasi hitung. Subjek ini memenuhi indikator kecemasan matematika yaitu kemampuan dan kepercayaan diri, sulit konsentrasi, takut gagal, gugup, kurang senang, gelisah, berkeringat dingin, jantung berdebar, sakit kepala.Kata Kunci :kesalahan; kecemasan; persamaan diferensial